Padrões citogenéticos em representantes de dois complexos de espécies de peixes com ocorrência em ecossistemas semiáridos neotropicais: Astyanax bimaculatus (Characidae) e Gymnotus carapo (Gymnotidae) - Costa, Jozenilda Francinilma da (2023)
Cytogenetic data from Neotropical fish have revealed numerous cryptic speciation processes, in allopatry, with particular emphasis on species with wide geographic distribution belonging to the Orders Characiformes and Gymnotiformes. Aiming to analyze possible cryptic diversifications in members of these clades in the Eastern Northeast Atlantic Basin, cytogenetic analyzes were carried out using Giemsa staining, Ag-RONs technique and C- banding, in Astyanax bimaculatus (Characidae) and Gymnotus carapo (Gymnotidae) from the river Pium (Parnamirim, Rio Grande do Norte), which integrate two recognized species complexes. A. bimaculatus exhibited 2n=50 chromosomes (8sm+14sm+18st+10a; NF=90) and G. carapo, 2n=44 chromosomes (12m+8sm+8st+16a; NF= 72). Heterochromatin in both species is distributed in the terminal and centromeric regions of the chromosomes. The Ag- RONs sites are simple, located in the short arms, respectively, of pairs 16 (submetacentric) and 8 (subtelocentric) of the species. The karyotypic patterns of “A. bimaculatus” and “G. carapo” from the Pium River, differ significantly, in terms of diploid number and karyotypic formula, from other populations of these species from other Brazilian river basins. The cytogenetic data reveal an unsuspected cryptic diversity and extend the phylogenetic extent of these species complexes to the Eastern Northeast Atlantic Basin.